IN VIVO ANTIMALARIAL ASSESSMENT AND PHYTOCHEMICAL COMPOSITION OF Carica papaya LEAF EXTRACT IN Plasmodium berghei-INFECTED MICE (FUDMA JOURNAL OF SCIENCES, 2025)
Malaria is one of the most devastating illnesses of all time and the most common parasitic disease in sub-Saharan Africa. Increasing resistance of Plasmodium species to currently used antimalarial drugs has necessitated the search for novel and more effective anti-malarial drugs from medicinal plants used in traditional medicine. This study aimed to quantify the phytochemical constituents and evaluate the antimalarial activity of the leaf extract of Carica papaya in established Plasmodium berghei infection in mice. Quantitative phytochemical analysis was carried out using conventional biochemical techniques. Mice infected with Plasmodium berghei were administered orally with the extract at doses of 100-500 mg/kg/day for five consecutive days. The extract significantly (p < 0.05) suppressed parasitemia in a dose-dependent manner, with the highest parasite inhibition (59.89%) observed at 500 mg/kg. Mean survival time (MST) ranged from 17.001.51 to 21.001.53 days in extract-treated groups, compared to 27.000.16 days and 27.331.00 days in chloroquine- and artesunate-treated groups, respectively, and 10.330.46 days in the untreated control. Quantitative phytochemical screening revealed appreciable levels of alkaloids (119.02.0 mg/g), saponins (42.00.67 mg/g), tannins (26.330.56 mg/g), flavonoids (24.500.79 mg/g), and phenols (6.520.24 mg/g). These findings demonstrate that C. papaya leaf extract possesses significant antiplasmodial activity, likely attributable to its rich alkaloid content, and suggest its potential as a promising source of alternative antimalarial agents.
Keywords: Carica papaya; Plasmodium berghei; Antimalarial activity; Phytochemical; Traditional medicine